Postać literacka i jej prawa - Bralczyk, Dominik (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The author ponders over a literary character, its position, form and significance in copyright law. He starts by defining a literary character. Next, he proceeds to a description of the criteria for a literary character ending his considerations on the issue of the self-containedness and identity of a literary character, as well as the issue of works inspired by others.